Aerobic Exercise Volume and Body Composition Changes Among Adults in a University in China - Lin, Ping (Pacific International Journal, 2025)
This study examines the relationship between aerobic exercise volume and body composition changes among adults aged 25-35 at a Chinese university. Aerobic exercise is widely recognized for its benefits on cardiovascular health and body composition, yet the optimal volume for this demographic remains underexplored. Utilizing a descriptive-comparative-correlational design, this research surveyed participants on their exercise habits—assessing frequency, intensity, and duration—and measured changes in key metrics like body fat percentage, muscle mass, and waist-to-hip ratio. Findings indicate a significant positive correlation between higher exercise volume and favorable improvements in body composition. Notably, participants engaging in consistent, long-term aerobic exercise demonstrated the most pronounced benefits. The study also reveals that while intentions for regular exercise are high, actual adherence varies, highlighting a gap between knowledge and practice. These results underscore the importance of structured, volume-focused aerobic programs tailored to this age group to maximize body composition outcomes. The research provides a foundation for developing personalized exercise prescriptions that can effectively address metabolic health and physical fitness in young adults.